Islamic Entrepreneurship: Al-Amin (Trustworthiness) and Al-Shidq (Truthfulness) as Personal Branding - Hilaluddin, Khaulah; Muhayiddin, Mohd Nazri; Muhammad, Mohd Zulkifli; Salleh, Muhammad Zulfaris Mohd; Nasir, Khairulnazrin; Rahman, Anis Amira Ab (Institut Agama Islam Sunan Giri Ponorogo, 2025)
Establishing a new business in Islamic entrepreneurship requires a holistic framework considering the entrepreneur’s traits, the organization they create, the environment, and the venture’s launch process. Through a case study based on hadith from the Prophet Muhammad (PBUH), this study investigates important traits of Muslim entrepreneurs. The study emphasizes the hadiths of maqbul (recognized), which provide direction and reassurance to Muslim entrepreneurs hoping for success and blessings in their ventures. According to the research, the entrepreneurial personality, as demonstrated by the Prophet (PBUH) and his companions, consists of qualities like Al-Amin (trustworthiness) and Al-Shidq (truthfulness), which are essential components of a personal branding strategy. This study demonstrates how these traits can positively impact economic performance, fostering trust and credibility in business practices. Al-Amin (trustworthiness) and Al-Shidq (truthfulness) are integral to personal branding in Islamic entrepreneurship. These values align with Islamic ethical principles and enhance business performance and organizational credibility. Entrepreneurs who embody these traits can build stronger, trustable brands, which are crucial to sustaining success in the competitive business environment. This study highlights the significance of these qualities by analyzing real-world examples from the lives of the Prophet (PBUH) and his companions. It offers Muslim entrepreneurs insightful guidance for their company’s growth.